Copper/Graphene/Clay Nanohybrid: A Highly Efficient Heterogeneous Nanocatalyst for the Synthesis of Novel 1, 2, 3‐Triazolyl Carboacyclic Nucleosides via 'Click' Huisgen 1, 3‐Dipolar Cycloaddition. Issue 9 (September 2015) - Navid Soltani Rad, Mohammad; Behrouz, Somayeh; Jafar Hoseini, S.; Nasrabadi, Hasan; Saberi Zare, Maryam
Abstract A very mild and highly efficient synthesis of some novel 1H‐1, 2, 3‐triazolyl carboacyclic nucleosides via a 'Click' Huisgen cycloaddition of N‐propargyl nucleobases and azido alcohols using Cu/aminoclay/reduced graphene oxide nanohybrid (Cu/AC/r‐GO nanohybrid) as nanocatalyst is described. The preparation and characterization of Cu/AC/r‐GO nanohybrid are discussed. This catalyst was characterized by X‐ray diffraction, FT‐IR, TEM, and energy‐dispersive analysis of X‐ray techniques. Cu/AC/r‐GO nanohybrid is a stable and highly efficient heterogeneous nanocatalyst that can be easily prepared, used, and restored from the reaction mixture by simple filtration, and reused for many consecutive trials without significant decrease in activity.